A high-energy-density full-tab cylindrical lithium-ion battery and an electric device

CN123034016APending Publication Date: 2026-11-03JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611222352.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

In existing technologies, there is a lack of systematic research on the synergistic matching of multiple parameters in the design of the all-tab structure, the application of silicon-carbon anodes, the optimization of cathode coatings, and the research on electrolyte additives. This results in deficiencies in high-energy-density batteries in terms of internal resistance, cycle life, and low-temperature performance.

Method used

By synergistically limiting the width ratio of the tab teeth to the negative electrode sheet, the content of deposited silicon and carbon, the thickness of the double-sided coating of the positive electrode, the compaction density of the negative electrode, and the content of fluoroethylene carbonate in the electrolyte in a full-tab cylindrical lithium-ion battery, a cross-parameter quantitative coupling relationship is constructed to achieve a balance between the current collection capacity of the tab and the expansion stress of silicon and carbon, and between the lithium-ion flux of the positive electrode and the interface stability of the electrolyte.

Benefits of technology

It achieves multiple goals such as high volumetric energy density, low internal resistance, long cycle life, excellent rate performance and good low temperature performance, improving the overall electrical performance of the battery and making it suitable for electric vehicles, energy storage systems and applications in cold regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of lithium ion battery, especially to a high-energy-density full-tab cylindrical lithium ion battery and an electric device. The full-tab cylindrical lithium ion battery comprises a positive cover plate, an explosion-proof valve, a shell and a roll core. The roll core comprises a positive electrode sheet, a negative electrode sheet, a separator and a full-tab structure. The full-tab structure is a tab tooth arranged on the edge of the electrode sheet without coating the current collector. The width ratio R of the tab tooth to the negative electrode sheet is 0.15-0.35. In the negative active material, the content S of the deposited silicon-carbon negative active material is 10%-30%. The double-sided coating thickness T of the positive electrode sheet is 80-120 μm. The compaction density D of the negative electrode sheet is 1.55-1.85 g / cm 3 . The content F of fluoroethylene carbonate is 8%-20% of the total mass of the electrolyte. The full-tab cylindrical lithium ion battery realizes high volumetric energy density, low internal resistance, long cycle life, excellent rate performance and good low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a high-energy-density all-tab cylindrical lithium-ion battery and its power application device. Background Technology

[0002] The rapid development of electric vehicles, energy storage systems, and high-end consumer electronics markets has placed higher demands on the energy density, power density, and safety performance of lithium-ion batteries. Cylindrical lithium-ion batteries occupy an important position in the power battery and energy storage fields due to their mature manufacturing processes, good consistency, high degree of automation, and flexible heat dissipation design. The all-tab cylindrical battery, a significant technological breakthrough in the cylindrical battery field in recent years, significantly shortens the current transmission path in the current collector by incorporating an all-tab structure in the uncoated area of ​​the electrode, thereby significantly reducing the battery's internal resistance and improving rate discharge performance and thermal safety. It has become an important development direction for high-energy-density cylindrical batteries.

[0003] In the field of high energy density cathode materials, high-nickel ternary material LiNi x Co y Mn z O2 (x≥0.8) has become the mainstream cathode material for high-energy-density batteries due to its high specific capacity and operating voltage. For anodes, deposited silicon-carbon composite materials, with their high specific capacity and controllable microstructure, represent an important development direction for next-generation high-energy-density anode materials. However, silicon-carbon anodes suffer from problems such as active material pulverization due to volume expansion during cycling and repeated rupture and regeneration of the solid electrolyte interphase (SEI) film. Therefore, it is crucial to combine the low internal resistance advantage of the all-tab structure with interface optimization using electrolyte additives to achieve a systematic and synergistic design.

[0004] Existing research has focused on aspects such as the design of the all-tab structure, the application of silicon-carbon anodes, the optimization of cathode coatings, the control of anode compaction, and the addition of fluoroethylene carbonate in the electrolyte. However, most of these studies focus on the independent optimization of single parameters, lacking systematic research on the synergistic matching of multiple key parameters. In particular, quantitative coupled studies are lacking on the balance between the low internal resistance characteristics brought by the all-tab structure and the expansion stress of the silicon-carbon anode, the trade-off between cathode coating thickness and rate performance, and the comprehensive impact of fluoroethylene carbonate content on low-temperature performance and cycle life.

[0005] Therefore, it is urgent to develop a technical solution for multi-parameter collaborative constraints, to construct a quantitative coupling relationship between various parameters, and to achieve compatible matching of multiple performance objectives that are mutually constrained within the same collaborative working window. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a high energy density all-tab cylindrical lithium-ion battery and power supply device.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A high-energy-density cylindrical lithium-ion battery with all tabs includes a positive electrode cover, an explosion-proof valve, a casing, and a core. The core includes a positive electrode sheet, a negative electrode sheet, a separator, and an all-tab structure. The all-tab structure consists of tab teeth disposed on the uncoated current collector edges of the positive and negative electrode sheets. The tab teeth are distributed along the length of the electrode sheets, and the width ratio R of the tab teeth to the negative electrode sheet is 0.15–0.35. In the negative electrode sheet, the content S of deposited silicon-carbon negative electrode active material is 10%–30% of the total mass of the negative electrode active material. The double-sided coating thickness T of the positive electrode sheet is 80–120 μm. The compaction density D of the negative electrode sheet is 1.55–1.85 g / cm³. 3 In the electrolyte of the all-tab cylindrical lithium-ion battery, the content of fluoroethylene carbonate F is 8% to 20% of the total mass of the electrolyte.

[0008] Based on the above technical solutions, preferably, the width ratio R and the deposited silicon-carbon content S satisfy R×S≤6.0%, where R is a decimal and S is a percentage.

[0009] Based on the above technical solutions, preferably, the thickness T of the positive electrode double-sided coating and the content F of the fluoroethylene carbonate satisfy T / F ≤ 10 μm / %, where T is expressed in μm and F is expressed as a percentage.

[0010] Based on the above technical solution, preferably, the positive electrode sheet comprises a high-nickel ternary positive electrode active material, and the chemical formula of the high-nickel ternary positive electrode active material is LiNi. x Co y Mn z O2, where 0.8 ≤ x ≤ 0.98, x + y + z = 1.

[0011] Based on the above technical solutions, preferably, the compaction density of the positive electrode sheet is 3.2–3.8 g / cm³. 3 .

[0012] Based on the above technical solutions, preferably, the areal density of the positive electrode sheet is 18–26 mg / cm². 2 The areal density of the negative electrode sheet on one side is 8–15 mg / cm³. 2 Furthermore, the ratio of the surface density of the positive electrode to the surface density of the negative electrode is 1:0.4 to 1:0.7.

[0013] Based on the above technical solutions, preferably, the porosity of the negative electrode sheet is 20% to 35%.

[0014] Based on the above technical solution, preferably, the deposited silicon-carbon anode active material comprises a porous carbon framework and deposited silicon distributed in the channels of the porous carbon framework, wherein the BET specific surface area of ​​the porous carbon framework is 200-1500 m². 2 / g, total pore volume is 0.4–1.8 cm³ 3 / g, wherein the deposited silicon accounts for 15% to 50% of the total mass of the deposited silicon-carbon anode active material. Based on the above technical solutions, preferably, the negative electrode active material further comprises a graphite-based negative electrode material, wherein the graphite-based negative electrode material is selected from natural graphite, artificial graphite, or a mixture of both, and the particle size D50 of the graphite-based negative electrode material is 8–20 μm, D90 ≤ 35 μm, and the BET specific surface area is 1.0–3.0 m². 2 / g.

[0015] The present invention also provides an electrical device, including the aforementioned all-tab cylindrical lithium-ion battery.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) By synergistically limiting the width ratio of the tab teeth to the negative electrode sheet, the content of deposited silicon carbon, the thickness of the double-sided coating of the positive electrode, the compaction density of the negative electrode and the content of fluoroethylene carbonate in the electrolyte, the present invention simultaneously achieves multiple objectives of high volumetric energy density, low internal resistance, long cycle life, excellent rate performance and good low temperature performance in a fully tabbed cylindrical battery.

[0017] (2) This invention transforms isolated parameter windows into a mutually matched and compensating synergistic system by constructing a cross-parameter quantitative coupling relationship between the current collection capacity of the electrode tab and the expansion stress of silicon-carbon, and between the lithium-ion flux of the cathode and the stability of the electrolyte interface. When the parameter that increases energy density approaches its upper limit, the corresponding coupling parameter simultaneously approaches its upper limit to compensate for its side effects, thereby maximizing energy density without exceeding any performance red lines of internal resistance, temperature rise, cycling, and low temperature. The limitation of this quantitative coupling boundary makes the process window clear and controllable, reduces product development cycle and manufacturing cost, and improves mass production consistency and yield.

[0018] (3) This invention achieves a combination of low internal resistance due to the all-tab structure, high capacity characteristics of the high-nickel ternary cathode, and high specific capacity of the deposited silicon-carbon anode. Combined with the optimization of the fluoroethylene carbonate content in the electrolyte, it takes into account high energy density, high power output capability, high safety margin due to low heat generation, and excellent wide temperature range adaptability. It is suitable for scenarios with stringent comprehensive performance requirements, such as electric vehicles, power tools, energy storage systems, and applications in cold regions. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention are purchased through commercial channels or synthesized from raw materials purchased through commercial channels.

[0021] A high-energy-density cylindrical lithium-ion battery with all tabs includes a positive electrode cover, an explosion-proof valve, a casing, and a core. The core includes a positive electrode sheet, a negative electrode sheet, a separator, and an all-tab structure. The all-tab structure consists of tab teeth disposed on the uncoated current collector edges of the positive and negative electrode sheets. The tab teeth are distributed along the length of the electrode sheets, and the width ratio R of the tab teeth to the negative electrode sheet is 0.15–0.35. In the negative electrode sheet, the content S of deposited silicon-carbon negative electrode active material is 10%–30% of the total mass of the negative electrode active material. The double-sided coating thickness T of the positive electrode sheet is 80–120 μm. The compaction density D of the negative electrode sheet is 1.55–1.85 g / cm³. 3 In the electrolyte of the all-tab cylindrical lithium-ion battery, the content of fluoroethylene carbonate F is 8% to 20% of the total mass of the electrolyte.

[0022] Specifically, the full tab structure is achieved as follows: tab teeth are continuously distributed along the length of the electrode sheet by laser cutting or die punching on the uncoated current collector edge of the electrode sheet. After winding, all positive electrode tab teeth converge at one end of the winding core and are welded to the positive electrode cover plate or positive electrode current collector plate, and all negative electrode tab teeth converge at the other end of the winding core and are welded to the bottom of the shell or negative electrode current collector plate. In the full tab structure, tab teeth are provided on the uncoated current collector edge of both the positive and negative electrode sheets. The tab width ratio R determines the competitive relationship between the tab current collection capacity and the active material area: if R is too small, the tab is too narrow, resulting in a serious lack of current collection capacity, increased internal resistance, and increased temperature rise, affecting battery safety and cycle life; if R is too large, the tab occupies too much electrode sheet area, the active material coating area is reduced, the energy density is reduced, and the overly wide tab is prone to wrinkles and misalignment during the winding process. The value of R can be 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, or 0.35, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] Specifically, silicon-carbon materials possess high specific capacity, which can significantly improve the energy density of the anode. However, if the content of deposited silicon-carbon anode active material is too high, the silicon undergoes significant volume expansion during lithium intercalation, leading to damage to the anode coating structure and repeated rupture and regeneration of the SEI film during cycling, resulting in a sharp decline in capacity retention. Conversely, if the content of deposited silicon-carbon anode active material is too low, the energy density improvement is not significant, making it difficult to meet the high energy density requirements. Controlling S between 10% and 30% fully utilizes the high capacity advantage of silicon-carbon materials while compensating for the local current unevenness caused by volume expansion through the low internal resistance characteristics of the all-tab, thus balancing energy density and cycle stability. The S can be selected from 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, and 30%, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0024] Specifically, the thickness of the double-sided coating of the positive electrode determines the loading of the positive electrode active material and the length of the lithium-ion diffusion path. While an excessively thick double-sided coating can increase the loading of active material per unit area, it also prolongs the diffusion path of lithium ions within the thick coating, increasing diffusion resistance, internal resistance, and rate performance. Conversely, an excessively thin double-sided coating results in insufficient active material loading and low energy density. Controlling T between 80 and 120 μm balances high active material loading with a reasonable lithium-ion diffusion path, achieving a balance between energy density and rate performance. T can be selected from values ​​of 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, and 120 μm, but is not limited to these values; other unlisted values ​​within this range are also applicable.

[0025] Specifically, the compaction density (D) of the negative electrode determines the packing density of the negative electrode active material and the contact state between particles. While excessively high compaction density can increase the content of active material per unit volume, excessive compaction pressure can lead to silicon-carbon particle breakage and collapse of the porous carbon framework, accelerating capacity decay. Conversely, excessively low compaction density results in loose contact between particles, high internal resistance, and a low volume fraction of active material, leading to insufficient energy density. The optimal compaction density is controlled between 1.55 and 1.85 g / cm³. 3 This design ensures sufficient interparticle electrical contact to reduce internal resistance while also allowing for some space for silicon volume expansion, thus balancing energy density and cycle stability. The D value can be selected as 1.55 g / cm³. 3 1.60 g / cm 3 1.65 g / cm 3 1.70 g / cm 3 1.75 g / cm 3 1.80 g / cm 3 1.85 g / cm 3 However, this does not limit the listed values; other unlisted values ​​within the range are also applicable.

[0026] Specifically, fluoroethylene carbonate (FEC) is an important film-forming additive in the electrolyte, and its content directly affects the chemical composition and physical properties of the negative electrode SEI film. If the content is too low, the LiF content in the SEI film is insufficient, resulting in a loose and unstable film structure. This leads to a sharp decrease in ionic conductivity at low temperatures, and the SEI film repeatedly ruptures and regenerates during cycling, accelerating capacity decay. If the content is too high, the electrolyte viscosity increases, ionic conductivity decreases, internal resistance rises, and excessive reduction of FEC leads to an excessively thick SEI film, reducing rate performance. Controlling the F content between 8% and 20% ensures the formation of a thin and dense SEI film rich in LiF to inhibit continuous electrolyte decomposition, while avoiding the adverse effects of excessive FEC on the electrolyte's ionic conductivity and internal resistance. The F content can be selected from 8%, 10%, 11%, 12%, 14%, 16%, 18%, and 20%, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0027] Based on the above technical solutions, preferably, the width ratio R and the deposited silicon-carbon content S satisfy R×S≤6.0%, where R is a decimal and S is a percentage.

[0028] Specifically, this coupling relationship represents a quantitative balance constraint between the current collection capacity of the full-tab electrode and the expansion stress of silicon-carbon. When the deposited silicon-carbon content S is high, the volume expansion increases, the internal resistance rises, and the pressure increases, requiring a wider tab (i.e., a larger R) to reduce internal resistance and heat generation, thereby mitigating the accelerated aging of the silicon-carbon interface due to thermal effects. Conversely, when S is low, the expansion stress is small, allowing R to be appropriately reduced to release more area for the active material. The boundary of R×S≤6.0% ensures that, under any combination, the low internal resistance characteristics of the full-tab electrode are sufficient to compensate for the local current non-uniformity problem caused by the volume expansion of the silicon-carbon anode. For example, when R=0.28 and S=20%, R×S=5.6%≤6.0%; when R=0.35 and S=15%, R×S=5.25%≤6.0%; when R=0.15 and S=30%, R×S=4.5%≤6.0%, but it is not limited to the listed values; other unlisted values ​​within the range also apply.

[0029] Based on the above technical solutions, preferably, the thickness T of the positive electrode double-sided coating and the content F of the fluoroethylene carbonate satisfy T / F ≤ 10 μm / %, where T is expressed in μm and F is expressed as a percentage.

[0030] Specifically, this coupling relationship represents a quantitative balance constraint between the cathode lithium-ion flux and the electrolyte interface stability. A thicker cathode coating generates a higher interfacial current density and a greater risk of side reactions during charge and discharge, requiring more fluoroethylene carbonate to maintain a stable interfacial film. The fluoroethylene carbonate content is limited by its upper limit on the electrolyte conductivity; excessive fluoroethylene carbonate increases electrolyte viscosity and internal resistance. Controlling T / F ≤ 10 μm / % ensures a quantitative match between the cathode coating thickness and the electrolyte film-forming additives. This allows the thick-coated cathode to obtain sufficient fluoroethylene carbonate to form a stable cathode-electrolyte interface (CEI) film, without sacrificing ionic conductivity due to excessive fluoroethylene carbonate. This approach helps balance cell energy density, cycle life, and rate performance, improving the overall electrochemical performance of the battery. For example, when T=100μm and F=14%, T / F≈7.14≤10; when T=120μm and F=20%, T / F=6≤10; when T=80μm and F=8%, T / F=10≤10, but not limited to the listed values, other unlisted values ​​within the range also apply.

[0031] Based on the above technical solution, preferably, the positive electrode sheet comprises a high-nickel ternary positive electrode active material, and the chemical formula of the high-nickel ternary positive electrode active material is LiNi. x Co y Mn z O2, where 0.8 ≤ x ≤ 0.98, x + y + z = 1.

[0032] Specifically, high-nickel ternary cathode materials possess high specific capacity due to their high nickel content, which is key to achieving high energy density. However, high-nickel materials also face problems such as reduced thermal stability and intensified surface side reactions. These issues require synergistic effects with the addition of fluoroethylene carbonate in the electrolyte and the heat dissipation advantages of the all-tab to suppress surface reconstruction and transition metal dissolution during cycling.

[0033] Based on the above technical solutions, preferably, the compaction density of the positive electrode sheet is 3.2–3.8 g / cm³. 3 .

[0034] Specifically, the compaction density of the positive electrode sheet determines the packing density of the positive electrode active material and the electrical contact state between particles. The compaction density of the positive electrode sheet should be controlled between 3.2 and 3.8 g / cm³. 3 This design ensures sufficient contact area between particles to reduce electronic resistance while preventing breakage of the high-nickel ternary particles due to excessive compaction, thus maintaining the particle integrity of the positive electrode active material. The compaction density of the positive electrode sheet can be selected as 3.2 g / cm³. 3 3.3 g / cm 3 3.4 g / cm 3 3.5 g / cm 3 3.6 g / cm 3 3.7 g / cm 3 3.8 g / cm 3 However, this does not limit the listed values; other unlisted values ​​within the range are also applicable.

[0035] Based on the above technical solutions, preferably, the areal density of the positive electrode sheet is 18–26 mg / cm². 2 The areal density of the negative electrode sheet on one side is 8–15 mg / cm³. 2 Furthermore, the ratio of the surface density of the positive electrode to the surface density of the negative electrode is 1:0.4 to 1:0.7.

[0036] Specifically, the areal density and ratio of the positive and negative electrodes determine the matching degree of the battery's positive and negative electrode capacities. If the areal density ratio is too high, meaning the negative electrode is relatively low, lithium ions released from the positive electrode during charging cannot be fully inserted into the negative electrode, leading to the precipitation of lithium dendrites on the negative electrode surface and causing safety hazards. If the areal density ratio is too low, meaning the negative electrode is relatively high, it will waste negative electrode capacity and reduce the overall energy density of the battery. The areal density of the positive electrode sheet can be selected as 18 mg / cm². 2 20 mg / cm 2 22mg / cm 2 24 mg / cm 2 26 mg / cm2 However, this does not limit the listed values; other unlisted values ​​within the range also apply. The areal density of the negative electrode sheet can be selected as 8 mg / cm³. 2 10 mg / cm 2 12 mg / cm 2 14 mg / cm 2 15mg / cm 2 However, the values ​​are not limited to those listed; other unlisted values ​​within the range are also applicable. The ratio of the surface density of the positive electrode sheet to the surface density of the negative electrode sheet can be 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, or 1:0.7, but is not limited to the listed ratios; other unlisted values ​​within the range are also applicable.

[0037] Based on the above technical solutions, preferably, the porosity of the negative electrode sheet is 20% to 35%.

[0038] Specifically, the porosity of the negative electrode directly affects the electrolyte wetting effect and lithium-ion transport efficiency. Too low a porosity leads to insufficient electrolyte wetting, hindered lithium-ion transport, and decreased rate performance and low-temperature performance; too high a porosity results in a sparse electronic conductivity network and reduced volumetric energy density. The porosity of the negative electrode can be selected from 20%, 22%, 25%, 28%, 30%, 32%, and 35%, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0039] Based on the above technical solution, preferably, the deposited silicon-carbon anode active material comprises a porous carbon framework and deposited silicon distributed in the channels of the porous carbon framework, wherein the BET specific surface area of ​​the porous carbon framework is 200-1500 m². 2 / g, total pore volume is 0.4–1.8 cm³. 3 / g, wherein the deposited silicon accounts for 15% to 50% of the total mass of the deposited silicon-carbon anode active material.

[0040] Specifically, nano-silicon is deposited within the pores of a porous carbon framework. The pores of the porous carbon framework provide a buffer space for the volume expansion of silicon. The BET specific surface area and total pore volume determine the silicon storage capacity and expansion buffer capacity of the carbon framework. If the specific surface area is too low or the pore volume is too small, the silicon loading is limited and the buffer space is insufficient. If the specific surface area is too high or the pore volume is too large, the tap density of the carbon framework is too low, affecting the volumetric energy density. The BET specific surface area of ​​the porous carbon framework can be selected to be 200 m². 2 / g、300 m 2 / g、500 m 2 / g、800 m 2 / g, 1000 m 2 / g、1200 m 2 / g, 1500 m 2 / g, but not limited to the listed values; other unlisted values ​​within the range also apply; the total pore volume can be selected as 0.4 cm³. 3 / g, 0.6cm 3 / g, 0.8 cm 3 / g, 1.0 cm 3 / g, 1.2 cm 3 / g, 1.5 cm 3 / g, 1.8 cm 3 / g, but not limited to the listed values, and other unlisted values ​​within the range are also applicable; the proportion of the deposited silicon to the total mass of the deposited silicon-carbon anode active material can be selected as 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, but not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0041] Based on the above technical solutions, preferably, the negative electrode active material further comprises a graphite-based negative electrode material, wherein the graphite-based negative electrode material is selected from natural graphite, artificial graphite, or a mixture of both, and the particle size D50 of the graphite-based negative electrode material is 8–20 μm, D90 ≤ 35 μm, and the BET specific surface area is 1.0–3.0 m². 2 / g.

[0042] Specifically, graphite-based anode materials are used in combination with deposited silicon-carbon materials. Graphite serves as the main matrix, providing stable cycle performance, while silicon-carbon materials provide high capacity. The particle size distribution of graphite affects the compaction density and rate performance of the anode sheet: a particle size range of D50 of 8–20 μm and D90 ≤ 35 μm ensures reasonable particle gradation and uniform dispersion, avoiding uneven coating surfaces caused by excessively large particles or excessively small particles leading to excessive specific surface area and exacerbated side reactions. The BET specific surface area of ​​graphite-based anode materials is 1.0–3.0 m² / g, ensuring adequate interfacial contact with the electrolyte. This avoids both the limitation of lithium intercalation kinetics caused by excessively low specific surface area and the excessive consumption of active lithium by interfacial side reactions caused by excessively high specific surface area. The D50 of the graphite-based anode material can be selected from 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, and 20μm, but is not limited to the listed values; other unlisted values ​​within the range are also applicable. The D90 can be selected from 20μm, 25μm, 28μm, 30μm, 32μm, and 35μm, but is not limited to the listed values; other unlisted values ​​within the range are also applicable. The BET specific surface area can be selected from 1.0 m². 2 / g, 1.5 m 2 / g, 2.0 m 2 / g, 2.5 m 2 / g, 3.0 m 2 / g, but not limited to the listed values; other unlisted values ​​within the range also apply.

[0043] The present invention also provides an electrical device, including the aforementioned all-tab cylindrical lithium-ion battery.

[0044] Specifically, the electrical device is one of the following: a power battery system, an energy storage battery system, a power tool, an electric vehicle, a drone, a portable electronic device, or an uninterruptible power supply.

[0045] The present invention will be further described below with reference to embodiments, but the present invention is not limited to the following embodiments. The present invention is illustrated using a 21650 all-tab cylindrical lithium-ion battery as an example, but those skilled in the art should understand that the technical solution of the present invention is not limited to the 21650 specification, and is equally applicable to other specifications of all-tab cylindrical lithium-ion batteries.

[0046] Example 1 This embodiment provides a high-energy-density, all-tab cylindrical lithium-ion battery, the preparation steps of which are as follows: S1, Preparation of positive electrode sheet NCM811 positive electrode active material (LiNi) 0.8 Co 0.1 Mn 0.1 O2, powder compaction density 3.4 g / cm³ 3 Conductive carbon black Super P and PVDF binder were mixed in NMP solvent at a mass ratio of 96:2:2 and dispersed using a dual planetary mixer under a vacuum of -0.09 MPa for 4 hours to obtain a positive electrode slurry with a solid content of 65%. The positive electrode slurry was then coated onto both sides of a 12 μm aluminum foil using a transfer coating machine at a coating speed of 4 m / min. After drying, the double-sided coating thickness T was measured to be 100 μm, and the single-sided areal density of the positive electrode was 22 mg / cm³. 2 The electrode sheets were pressed using a roller press at 80°C to a compaction density of 3.6 g / cm³. 3 The electrode sheets are cut into 58mm wide plates, with an 8mm uncoated area reserved for tab forming.

[0047] S2, Preparation of negative electrode sheet Silicon-carbon anode active material (silicon content 30wt%, prepared by CVD method, porous carbon framework BET 850 m) was deposited. 2 / g, total pore volume 1.2 cm³ 3 / g) and artificial graphite (D50=12μm, BET 1.8 m) 2The negative electrode active material was obtained by mixing (g) at a mass ratio of 20:80 (i.e., S = 20%). The negative electrode active material (94.5 wt%), conductive carbon black Super P (1.5 wt%), sodium carboxymethyl cellulose (1.5 wt%), and styrene-butadiene rubber (2.5 wt%) were added to deionized water and dispersed in a vacuum mixer for 3 hours to obtain a negative electrode slurry with a solid content of 48%. The negative electrode slurry was then coated onto both sides of an 8 μm copper foil using a comma-shaped doctor blade coater, with a single-sided areal density of 12 mg / cm³. 2 The coating speed was 3 m / min. After drying, the coating was rolled at room temperature until the compacted density D was 1.70 g / cm³. 3 The electrode sheets are cut into 60mm wide plates, with an 8mm uncoated area reserved for tab forming.

[0048] S3, All-Electrode Molding A laser tab forming machine (fiber laser, wavelength 1064nm, power 30W) was used to laser-cut the uncoated current collector edges of the positive and negative electrode sheets, forming tab teeth continuously distributed along the length of the electrode sheets. The tab teeth are 6mm high and 16.8mm wide (the width ratio of the tab teeth to the negative electrode sheet R = 16.8 / 60 = 0.28), with a spacing of 2mm between adjacent tab teeth. After the positive and negative electrode sheets are formed, a CCD vision inspection system is used to check the size and positional accuracy of the tabs.

[0049] S4, winding The positive and negative electrode sheets, along with a 12μm ceramic-coated PE separator (40% porosity, 200s / 100mL air permeability), are wound on an automatic winding machine to form a 21650 specification core. The core has an outer diameter of 19.0mm and a height of 60mm. During the winding process, the positive and negative electrode tabs are aligned at both ends of the core.

[0050] S5, In-shell welding The core is inserted into a nickel-plated steel shell with a diameter of 21mm, a height of 65mm, and a wall thickness of 0.30mm. The positive electrode lugs are welded to the positive current collector using an ultrasonic welding machine at a power of 800W for 0.3s; the negative electrode lugs are welded to the bottom of the shell at a power of 1000W for 0.5s. The positive electrode cover and explosion-proof valve are installed, and the positive electrode cover is sealed to the shell using laser sealing welding.

[0051] S6, liquefaction component capacity Electrolyte was injected into a glove box (H2O < 1 ppm, O2 < 1 ppm) at an injection rate of 3.2 g / Ah, and then allowed to stand for 24 hours. Formation was performed by constant current charging at 0.05 C to 4.25 V at 45 °C, followed by aging at 60 °C for 48 hours. Finally, capacity was determined by capacity testing at 25 °C (0.2 C charge-discharge cycle for one week).

[0052] Electrolyte preparation: Ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1:1 to prepare a mixed organic solvent. Lithium salt (LiPF6, 1.2 mol / L) was dissolved in the mixed organic solvent, and 14 wt% fluoroethylene carbonate, 1 wt% vinylene carbonate and 1 wt% 1,3-propane sulpholol were added as additives to prepare the electrolyte.

[0053] Example 2 The difference between this embodiment and embodiment 1 is that in step S3, the width of the electrode teeth is controlled to be 9.0 mm and R = 9.0 / 60 = 0.15 during the forming of the full electrode tab. The rest is the same as in embodiment 1.

[0054] Example 3 The difference between this embodiment and embodiment 1 is that in step S3, the width of the electrode teeth is controlled to be 13.2 mm when the full electrode is formed, and R = 13.2 / 60 = 0.22. The rest is the same as in embodiment 1.

[0055] Example 4 The difference between this embodiment and embodiment 1 is that in step S3, the width of the electrode teeth is controlled to be 21.0 mm and R = 21.0 / 60 = 0.35 during the forming of the full electrode tab. The rest is the same as in embodiment 1.

[0056] Example 5 The difference between this embodiment and embodiment 1 is that in step S2, the mass ratio of the deposited silicon-carbon anode active material to artificial graphite is adjusted to 10:90, i.e., S = 10%, and the rest is the same as in embodiment 1.

[0057] Example 6 The difference between this embodiment and embodiment 1 is that in step S2, the mass ratio of the deposited silicon-carbon anode active material to artificial graphite is adjusted to 15:85, i.e., S = 15%, and the rest is the same as in embodiment 1.

[0058] Example 7 The difference between this embodiment and embodiment 1 is that in step S2, the mass ratio of the deposited silicon-carbon anode active material to artificial graphite is adjusted to 30:70, i.e., S = 30%, and the rest is the same as in embodiment 1.

[0059] Example 8 The difference between this embodiment and Embodiment 1 is that in step S1, the thickness T of the double-sided coating is controlled to be 80 μm during the positive electrode coating process, while the rest is the same as in Embodiment 1.

[0060] Example 9 The difference between this embodiment and Embodiment 1 is that in step S1, the thickness T of the double-sided coating is controlled to be 95 μm during the positive electrode coating process, while the rest is the same as in Embodiment 1.

[0061] Example 10 The difference between this embodiment and Embodiment 1 is that in step S1, the thickness T of the double-sided coating is controlled to be 120 μm during the positive electrode coating process, while the rest is the same as in Embodiment 1.

[0062] Example 11 The difference between this embodiment and Embodiment 1 is that in step S2, the compaction density D is controlled to be 1.55 g / cm³ during the rolling process. 3 The rest is the same as in Example 1.

[0063] Example 12 The difference between this embodiment and Embodiment 1 is that in step S2, the compaction density D is controlled to be 1.65 g / cm³ during the rolling process. 3 The rest is the same as in Example 1.

[0064] Example 13 The difference between this embodiment and Embodiment 1 is that in step S2, the compaction density D is controlled to be 1.85 g / cm³ during the rolling process. 3 The rest is the same as in Example 1.

[0065] Example 14 The difference between this embodiment and Embodiment 1 is that in step S6, 8 wt% of fluoroethylene carbonate is added during electrolyte preparation, while the rest is the same as in Embodiment 1.

[0066] Example 15 The difference between this embodiment and Embodiment 1 is that in step S6, 11 wt% of fluoroethylene carbonate is added during electrolyte preparation, while the rest is the same as in Embodiment 1.

[0067] Example 16 The difference between this embodiment and Embodiment 1 is that in step S6, 20 wt% of fluoroethylene carbonate is added during electrolyte preparation, while the rest is the same as in Embodiment 1.

[0068] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S3, the width of the electrode teeth is controlled to be 4.8 mm and R = 4.8 / 60 = 0.08 during the forming of the full electrode tab. The rest is the same as in Example 1.

[0069] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S3, the width of the tab teeth is controlled to be 27.0 mm when the full tab is formed, and R = 27.0 / 60 = 0.45. The rest is the same as in Example 1.

[0070] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S2, the mass ratio of the deposited silicon-carbon anode active material to artificial graphite is adjusted to 5:95, i.e., S = 5%, while the rest is the same as in Example 1.

[0071] Comparative Example 4 The difference between this comparative example and Example 1 is that in step S2, the mass ratio of the deposited silicon-carbon anode active material to artificial graphite is adjusted to 40:60, i.e., S = 40%, while the rest is the same as in Example 1.

[0072] Comparative Example 5 The difference between this comparative example and Example 1 is that in step S1, the thickness T of the double-sided coating is controlled to be 60 μm during the positive electrode coating process, while the rest is the same as in Example 1.

[0073] Comparative Example 6 The difference between this comparative example and Example 1 is that in step S1, the thickness T of the double-sided coating is controlled to be 150 μm during the positive electrode coating process, while the rest is the same as in Example 1.

[0074] Comparative Example 7 The difference between this comparative example and Example 1 is that in step S2, the compaction density D is controlled to be 1.40 g / cm³ during the rolling process. 3 The rest is the same as in Example 1.

[0075] Comparative Example 8 The difference between this comparative example and Example 1 is that in step S2, the compaction density D is controlled to be 2.00 g / cm³ during the rolling process. 3 The rest is the same as in Example 1.

[0076] Comparative Example 9 The difference between this comparative example and Example 1 is that in step S6, 3 wt% of fluoroethylene carbonate is added during electrolyte preparation, while the rest is the same as in Example 1.

[0077] Comparative Example 10 The difference between this comparative example and Example 1 is that in step S6, 30 wt% of fluoroethylene carbonate is added during electrolyte preparation, while the rest is the same as in Example 1.

[0078] Battery parameter testing: The width ratio R of the tab to the electrode sheet was measured using an optical microscope, taking the arithmetic mean of at least 10 measurement points at different locations; the content S of the deposited silicon-carbon anode active material was determined using thermogravimetric analysis (air atmosphere, room temperature to 1000℃, heating rate 10℃ / min) combined with inductively coupled plasma atomic emission spectrometry, and the mass ratio of the deposited silicon-carbon anode active material was calculated from the silicon content; the thickness T of the double-sided coating of the positive electrode sheet was measured using a micrometer or scanning electron microscope cross-sectional observation method, taking the arithmetic mean of at least 10 measurement points evenly distributed along the length of the electrode sheet; the compaction density D of the negative electrode was calculated by dividing the coating mass per unit area by the coating thickness, with the coating mass per unit area determined by weighing and the coating thickness determined by a micrometer, taking the average of at least 5 samples; the content F of fluoroethylene carbonate in the electrolyte was determined by the peak area ratio of the characteristic peak of fluoroethylene carbonate using gas chromatography-mass spectrometry or ion chromatography.

[0079] Performance testing methods (1) First Coulomb Efficiency (ICE) Test The formed all-tab cylindrical battery was left to stand at 25±2℃ for at least 4 hours to reach thermal equilibrium; then it was charged at a constant current of 0.1C to the cutoff voltage of 4.25V, and then discharged at a constant current of 0.1C to the cutoff voltage of 2.5V. The initial charge capacity Q was recorded. charge With the first discharge capacity Q discharge According to the formula ICE = Q discharge / Q charge Calculate the initial coulombic efficiency by multiplying by 100%. Repeat the test on 3 batteries for each sample and take the average value. If the relative deviation exceeds 2%, retest.

[0080] (2) Volumetric energy density and mass energy density test After the battery undergoes 1C / 1C capacity testing, its mass m (including the casing and cover) is weighed using an electronic balance with an accuracy of not less than 0.01g. The outer diameter D and height H of the battery are measured using a vernier caliper with an accuracy of not less than 0.01mm, and the result is calculated as V = π×(D / 2). 2 Calculate the battery volume V using ×H; discharge at 1C constant current to the cutoff voltage of 2.5V at 25±2℃, and record the 1C discharge capacity C (unit: Ah); calculate the mass energy density (Wh / kg, 3.7V is the median voltage of the plateau) using the mass energy density = C×3.7 / m, and calculate the volume energy density (Wh / L) using the volume energy density = C×3.7 / V; test 3 samples for each sample and take the average value.

[0081] (3) AC internal resistance (AC 1kHz) test The battery was discharged at a constant current of 0.5C to 50% state of charge (SOC) in an environment of 25±2℃. After standing for 1 hour, a sinusoidal AC excitation signal with a frequency of 1kHz and an amplitude of ≤10mV (rms) was applied using an AC impedance spectrometer to measure the real part of the battery's AC impedance (i.e., AC internal resistance / ESR). The test was carried out in a constant temperature chamber, with the positive and negative terminals of the battery in reliable contact with the four-probe clamp. Three samples were tested for each sample, and the average value was taken. The result is expressed in milliohms (mΩ).

[0082] (4) Cycle life (capacity retention rate at 500 cycles) test The battery was charged to 4.25V at 1C constant current and constant voltage (cutoff current 0.05C) in an environment of 25±2℃, and then discharged to 2.5V at 1C constant current, which was recorded as one cycle. The above charge and discharge cycle was repeated, and the capacity was calibrated every 100 cycles. After 500 cycles, the discharge capacity C of the 500th cycle was recorded. 500 Compared with the initial discharge capacity C0, the capacity retention rate = C 500 / C0× 100% to calculate the capacity retention rate over 500 weeks; three batteries were tested for each sample and the average value was taken, with the ambient temperature and humidity controlled (temperature 25±2℃, relative humidity ≤60%).

[0083] (5) Rate performance (3C discharge capacity retention rate) test The battery was first charged at 25±2℃ using a 1C constant current and constant voltage to 4.25V (cutoff current 0.05C), and then discharged at a 3C constant current to the cutoff voltage of 2.5V. The 3C discharge capacity C was recorded. 3C After being fully charged using the same charging regime, the reference capacity C was recorded by discharging at a constant current of 1C to 2.5V. base According to 3C capacity retention rate = C 3C / C base × 100% to calculate the rate discharge capacity retention rate; during the test, ensure that the initial temperature of the battery surface is consistent (25±2℃), and repeat the test 3 times for each sample and take the average value.

[0084] (6) Discharge temperature rise (1C discharge temperature rise) test The battery was placed in a constant temperature chamber at 25±1℃ for at least 4 hours to allow the battery core and surface temperature to uniformly reach the ambient temperature T0. While maintaining the temperature in the chamber at 25±1℃, it was discharged at a constant current of 1C to the cutoff voltage of 2.5V. Throughout the discharge process, a thermocouple or infrared thermometer attached to the battery surface (from the middle of the casing) was used to record the highest surface temperature T in real time. max According to the temperature rise ΔT = T max - T0 is used to calculate the 1C discharge temperature rise. Three samples are tested for each sample and the average value is taken.

[0085] (7) Low temperature performance (capacity retention rate at -20℃) test The battery was charged at 25±2℃ with a constant current and constant voltage of 1C to 4.25V (cutoff current 0.05C), then transferred to a -20±2℃ low-temperature chamber and left to stand for more than 4 hours to reach thermal equilibrium; subsequently, it was discharged at -20℃ with a constant current of 0.5C to a cutoff voltage of 2.0V, and the low-temperature discharge capacity C was recorded. low After removing the battery and restoring it to 25°C, fully charge it using the same charging regime and discharge it at 1C to 2.5V, recording the room temperature reference capacity C. 25 According to the low-temperature capacity retention rate = C low / C 25 Calculate the capacity retention rate at -20℃ by multiplying by 100%. Test 3 samples for each sample and take the average value.

[0086] The initial coulombic efficiency, volumetric energy density, internal resistance, 500-cycle capacity retention, discharge temperature rise, -20℃ low-temperature capacity retention, and 3C rate capacity retention of the all-tab cylindrical lithium-ion batteries obtained in Examples 1-16 and Comparative Examples 1-10 were tested. The results are shown in Table 1.

[0087] Table 1 Performance test results of all-tab cylindrical batteries in Examples 1-16 and Comparative Examples 1-10 Comparing the test results of Examples 1-4 with those of Comparative Examples 1-2, it can be seen that: increasing the tab width ratio increases the current collection area of ​​the tab, shortens the electron transmission path, and reduces the internal resistance and temperature rise, thereby improving the rate performance; however, an excessively large tab width ratio will encroach on the coating area of ​​the active material, resulting in a decrease in energy density and poor winding alignment, while an excessively small tab width ratio will result in insufficient current collection and a significant increase in internal resistance and temperature rise.

[0088] Comparing the test results of Examples 1, 5-7 with those of Comparative Examples 3-4, it can be seen that increasing the content of deposited silicon-carbon anode active material can significantly improve the anode capacity and battery energy density, but the volume expansion of silicon will intensify, leading to a decrease in ICE and accelerated cycle decay. If the content of deposited silicon-carbon anode active material is too low, the energy density improvement will be limited, while if the content of deposited silicon-carbon anode active material is too high, the cycle structure will be damaged and the capacity will plummet.

[0089] Comparing the test results of Examples 1, 8-10 with those of Comparative Examples 5-6, it can be seen that: increasing the thickness of the double-sided coating of the positive electrode increases the active material loading and energy density, but the lengthening of the lithium-ion diffusion path leads to increased internal resistance and decreased rate performance; if the double-sided coating of the positive electrode is too thin, the energy density is insufficient, and if the double-sided coating of the positive electrode is too thick, polarization is aggravated and cycle decay is accelerated.

[0090] Comparing the test results of Examples 1, 11-13 with those of Comparative Examples 7-8, it can be seen that increasing the compaction density of the negative electrode increases the content of active material per unit volume and improves the conductivity between particles, which is beneficial to improving energy density and reducing internal resistance. However, excessively high compaction density of the negative electrode will cause silicon-carbon particles to break and carbon skeleton to collapse, resulting in a sharp deterioration in cycle stability. Conversely, excessively low compaction density of the negative electrode will result in a loose conductive network and high internal resistance.

[0091] Comparing the test results of Examples 1, 14-16 with those of Comparative Examples 9-10, it can be seen that: increasing the content of fluoroethylene carbonate is beneficial to the formation of a dense SEI film rich in LiF, which significantly improves cycle life and low-temperature performance; however, excessive fluoroethylene carbonate will increase the viscosity of the electrolyte and raise the internal resistance. An excessively thick SEI film will degrade the rate performance, while an excessively low content of fluoroethylene carbonate will result in a loose and unstable SEI film, leading to a sharp decline in cycle and low-temperature performance.

[0092] This invention establishes a quantitative coupling relationship between the tab width ratio and the content of deposited silicon and carbon, as well as a quantitative coupling relationship between the thickness of the cathode coating and the content of fluoroethylene carbonate. By constraining five independent parameters within the same synergistic feasible domain, it enables the simultaneous achievement of conflicting performance objectives such as high energy density, low internal resistance, long cycle life, low temperature availability, and low heat generation.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-energy-density all-tab cylindrical lithium-ion battery, comprising a positive electrode cover, an explosion-proof valve, a casing, and a core, wherein the core comprises a positive electrode sheet, a negative electrode sheet, a separator, and an all-tab structure, wherein the all-tab structure consists of tab teeth disposed on the uncoated current collector edges of the positive and negative electrode sheets, the tab teeth being distributed along the length of the electrode sheets, characterized in that: The width ratio R between the tab teeth and the negative electrode plate is 0.15 to 0.35; In the negative electrode active material of the negative electrode sheet, the content S of the deposited silicon-carbon negative electrode active material is 10% to 30% of the total mass of the negative electrode active material; The thickness T of the double-sided coating of the positive electrode sheet is 80-120 μm; The compaction density D of the negative electrode sheet is 1.55–1.85 g / cm³. 3 ; In the electrolyte of the all-tab cylindrical lithium-ion battery, the content of fluoroethylene carbonate F is 8% to 20% of the total mass of the electrolyte.

2. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The width ratio R and the deposited silicon-carbon content S satisfy R × S ≤ 6.0%, where R is a decimal and S is a percentage.

3. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The thickness T of the positive electrode double-sided coating and the content F of the fluoroethylene carbonate satisfy T / F ≤ 10 μm / %, where T is in μm and F is in percentage.

4. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The positive electrode sheet comprises a high-nickel ternary positive electrode active material, the chemical formula of which is LiNi. x Co y Mn z O2, where 0.8 ≤ x ≤ 0.98, x + y + z = 1.

5. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 3.2–3.8 g / cm³. 3 .

6. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The areal density of the positive electrode sheet is 18–26 mg / cm³. 2 The areal density of the negative electrode sheet on one side is 8–15 mg / cm³. 2 Furthermore, the ratio of the surface density of the positive electrode to the surface density of the negative electrode is 1:0.4 to 1:0.

7.

7. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The porosity of the negative electrode sheet is 20% to 35%.

8. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The deposited silicon-carbon anode active material comprises a porous carbon framework and deposited silicon distributed in the channels of the porous carbon framework, wherein the BET specific surface area of ​​the porous carbon framework is 200–1500 m². 2 / g, total pore volume is 0.4–1.8 cm³ 3 / g, wherein the deposited silicon accounts for 15% to 50% of the total mass of the deposited silicon-carbon anode active material.

9. The all-tab cylindrical lithium-ion battery according to claim 1, characterized in that: The negative electrode active material further comprises a graphite-based negative electrode material, which is selected from natural graphite, artificial graphite, or a mixture of both. The graphite-based negative electrode material has a particle size D50 of 8–20 μm, a D90 ≤ 35 μm, and a BET specific surface area of ​​1.0–3.0 m². 2 / g.

10. An electrical device, characterized in that, Includes the all-tab cylindrical lithium-ion battery as described in any one of claims 1-9.